2001
DOI: 10.1073/pnas.121173298
|View full text |Cite
|
Sign up to set email alerts
|

Akt suppresses androgen-induced apoptosis by phosphorylating and inhibiting androgen receptor

Abstract: Whereas several apoptosis-related proteins have been linked to the antiapoptotic effects of Akt serine-threonine kinase, the search continues to explain the Akt signaling role in promoting cell survival via antiapoptotic effects. Here, we demonstrate that Akt phosphorylates the androgen receptor (AR) at Ser-210 and Ser-790. A mutation at AR Ser-210 results in the reversal of Akt-mediated suppression of AR transactivation. Activation of the phosphatidylinositol-3-OH kinase͞Akt pathway results in the suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
287
2
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(314 citation statements)
references
References 36 publications
15
287
2
4
Order By: Relevance
“…Sequence analysis of AR reveals two Akt consensus sequences (RXRXXS/T; Wen et al, 2000), thus Akt can interact directly with AR leading to its phosphorylation (Wen et al, 2000;Lin et al, 2001Lin et al, , 2002. We also observed that isosilybin B treatment results in the activation of Akt as evident by its increased phosphorylation and an increase in Akt kinase activity ( Figure 6b) along with an increased binding between Akt and AR ( Figure 6c).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Sequence analysis of AR reveals two Akt consensus sequences (RXRXXS/T; Wen et al, 2000), thus Akt can interact directly with AR leading to its phosphorylation (Wen et al, 2000;Lin et al, 2001Lin et al, , 2002. We also observed that isosilybin B treatment results in the activation of Akt as evident by its increased phosphorylation and an increase in Akt kinase activity ( Figure 6b) along with an increased binding between Akt and AR ( Figure 6c).…”
Section: Discussionmentioning
confidence: 53%
“…Isosilybin B increases the phosphorylation of Akt Akt (60 kDa) is one such kinase whose role has been described in the phosphorylation and degradation of AR (Lin et al, 2001(Lin et al, , 2002. Therefore, we next examined the effect of isosilybin B treatment on Akt phosphorylation.…”
Section: Isosilybin B Induces G 1 Arrest In Serum-and Androgen-stimulmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, increased androgen receptor expression, by whatever mechanism, can at best only explain hormone resistance in a subgroup of prostate cancer cases. Alternative mechanisms of hormone resistance are activation of AR via phosphorylation (Zhu and Liu 1997;Lin et al, 2001), therefore increasing AR activity without effecting its expression levels or may bypass the AR, for example, AP-1 phosphorylation (Henttu and Vihko, 1998;Krishna et al, 2002).…”
Section: Discussionmentioning
confidence: 99%